The Influence of Eco-Investment on E-Waste Recycling-Evidence From EU Countries - Constantinescu, Andreea; Platon, Victor; Surugiu, Marius; Frone, Simona; Antonescu, Daniela; Mazilescu, Raluca (Frontiers in Environmental Science, 2022)
Waste electrical and electronic equipment is the fastest growing waste stream internationally. Due to their physical characteristics, e-waste is a suitable subject for the development of recovery, repair and recycling policies, prolonging their life cycle for as long as possible, being an objective pursued by the specific mechanisms of the circular economy. From the point of view of economic development models, e-waste management is one of the areas with significant potential for implementation of circular economy. In this paper, we will analyse how one of the circular economy indicators, namely the eco-investment, influences e-waste management in European Union. An econometric model regarding the influence of eco-investments on e-waste recycling in EU Member States will highlight the impact of circular economy indicators and the importance of promoting the reduce-reuse-recycle paradigm, especially for e-waste. The results of the econometric analysis performed show that all member states of European Union benefit from eco-investment in a different degree and it is a strong influencing factor for e-waste recycling.